2002
DOI: 10.1038/sj.jea.7500235
|View full text |Cite
|
Sign up to set email alerts
|

Sampling private wells at past homes to estimate arsenic exposure: A methodologic study in New England

Abstract: We are conducting a collaborative, population -based case -control study in Maine, New Hampshire, and Vermont to investigate the reasons for the elevated bladder cancer mortality in northern New England. Arsenic in drinking water is one of the primary exposures under investigation. To estimate subjects' lifetime exposure to waterborne arsenic, it will be necessary to obtain water samples from private wells that subjects used in the past. We conducted a methodologic study to assess the feasibility of locating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, such measurements often are not available or feasible (30). Several studies have identified localized contamination, but none have related arsenic occurrence to predictor variables in New England.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, such measurements often are not available or feasible (30). Several studies have identified localized contamination, but none have related arsenic occurrence to predictor variables in New England.…”
Section: Discussionmentioning
confidence: 96%
“…A prediction model, however, is necessary to estimate arsenic levels of water from wells at past homes that cannot be directly measured. In a pilot study, 53% of past residences fell into this category (30).…”
Section: Introductionmentioning
confidence: 99%
“…Further, for some contaminants, including arsenic [21], a test strip or other in-the-field method suitable for study participants does not exist. Also, it is not always feasible to obtain water from the residence of interest [22], and use of records might allow one to consider past contaminant levels, including those at past residences. The importance of this has been documented [23].…”
Section: Discussionmentioning
confidence: 99%
“…In this study area, signiWcant exposures to arsenic have occurred in the recent past, and are still occurring, although government intervention has reduced some exposures (Colt et al 2002;Shimokura et al 1998;Lindberg et al 2006). …”
Section: Introductionmentioning
confidence: 97%
“…This can introduce exposure misclassiWcation compared to individual-level indices (Colt et al 2002;Ryan et al 2000).…”
Section: Introductionmentioning
confidence: 98%